The Intake of Total Digestible Nutrient, Digestibility of Dry Matter and Organic Matter of Lactating Cows that Get Supplements of Curcuma xanthorriza Roxb - Yusuf Wili Prihantoro; Anis Muktiani; Dian Wahyu Harjanti (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The study aimed to examine the effect of herbal supplement in the form of curcuma flour on intake of total digestible nutrient, dry matter and organic matter digestibility of lactation cows. The material used was 12 lactating cows. The study used a randomized block design with 2 treatments and 6 groups based on milk production. The treatments applied were T0 = basal feed and T1 = basal feed + curcuma supplement (1% DM). The parameters observed included the amount of feed consumption and digestibility of dry matter and organic matter. The data obtained were analyzed using ANOVA. The results of this study showed that the addition of 1% curcuma supplement (1% DM) into the diets of lactating cows has no significant effect (P> 0.05) on total intake of digestible nutrient, dry matter and organic matter digestibility. The average of TDN intake in T0 and T1 were 10.61 kg and 10.67 kg on DM basis, respectively. The dry matter digestibility of T0 and T1 groups were 60.89% and 59.20%, respectively. The organic matter digestibility in T0 and T1 were 57.46% and 55.59%, respectively. The addition of curcuma supplement 1% of DM in the diet of lactating cows has not been able to increase the intake of total digestible nutrient, dry matter and organic matter digestibility.